A rapid and green preparation method of cellulose nanocrystals based on mixed ionic liquid system
Patent Information
- Application Number
- CN202611500072.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-11-03
AI Technical Summary
Existing methods for preparing cellulose nanocrystals are inefficient, cause heavy environmental pollution, and have poor raw material adaptability. Traditional processes rely on high-purity raw materials and consume a lot of energy, making it difficult to meet the requirements of green and sustainable manufacturing.
By employing a hybrid ionic liquid system, the rapid and green preparation of cellulose nanocrystals is achieved through the synergistic effect of a dissolving/swelling ionic liquid that disrupts hydrogen bonds in cellulose and an acidic ionic liquid that catalyzes the breaking of glycosidic bonds, directly processing all components of biomass raw materials.
Shorten reaction time, improve reaction accessibility, reduce production costs, achieve efficient utilization of various cellulose raw materials, and make ionic liquids reusable, thus reducing environmental impact.
Smart Images

Figure CN123026727A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials and nanotechnology. Background Technology
[0002] Lignocellulose is the most abundant renewable biomass resource on Earth, widely found in plant cell walls, with a global annual production of approximately 180 billion tons. Compared to traditional petroleum-based synthetic polymers, cellulose possesses characteristics such as renewability, good biocompatibility, ease of surface modification, and biodegradability. However, current development and utilization of cellulose are mainly concentrated in traditional fields such as papermaking and wood processing, and its potential for high-value-added applications has not been fully explored. In recent years, with the rapid development of nanotechnology in materials science, research on lignocellulose-based nanomaterials has attracted much attention. Cellulose nanocrystals (CNCs), as rigid rod-shaped nanoparticles, not only inherit the good biodegradability and biocompatibility of natural cellulose but also exhibit unique physicochemical properties, including high crystallinity, high specific surface area, high aspect ratio, and excellent mechanical properties (theoretical elastic modulus can reach 150 GPa). These superior properties make them promising for applications in nanocomposite reinforcement phases, biomedical carriers, rheology modifiers, and optoelectronic functional materials.
[0003] Despite the promising application prospects of CNCs, existing preparation technologies still face numerous bottlenecks hindering their industrialization. While the mainstream strong acid hydrolysis method is mature, it suffers from problems such as equipment corrosion, difficult waste disposal, and low yield. In particular, the sulfonic acid groups introduced by sulfuric acid hydrolysis, although improving water dispersibility, significantly reduce the thermal stability of CNCs. Although TEMPO oxidation can achieve surface carboxylation, its dependence on expensive and biotoxic chemical reagents (such as TEMPO and sodium bromide) and stringent process control requirements pose challenges for low-cost large-scale production. Furthermore, these traditional processes typically require high purity raw materials (often relying on high-purity pulp or microcrystalline cellulose) and are often accompanied by long reaction cycles and high energy consumption, making it difficult to meet the requirements of green and sustainable manufacturing.
[0004] To address the aforementioned issues, developing a green preparation process that can directly process primary biomass (such as poplar wood powder and corn stalks), reacts rapidly, and uses recyclable solvents has become a key technical challenge that urgently needs to be overcome in this field. Summary of the Invention
[0005] This invention aims to address the problems of low efficiency, heavy environmental pollution, and poor raw material adaptability in existing methods for preparing cellulose nanocrystals, and to provide a rapid and green method for preparing cellulose nanocrystals based on a mixed ionic liquid system.
[0006] A rapid and green method for preparing cellulose nanocrystals based on a mixed ionic liquid system is described, comprising the following steps:
[0007] 1. A dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose and an acidic ionic liquid that catalyzes the breaking of glycosidic bonds are heated and mixed evenly to obtain a mixed ionic liquid. The lignocellulose raw material is added to the mixed ionic liquid to react and obtain a reaction system. The antisolvent is added to the reaction system to terminate the reaction and obtain a diluted reaction system.
[0008] Second, the diluted reaction system is allowed to stand, then centrifuged multiple times, and finally the solid product is added to a solvent for mechanical treatment, thus completing the rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system.
[0009] The beneficial effects of this invention are:
[0010] (1) The present invention utilizes a dissolving / swelling ionic liquid that disrupts the hydrogen bonds of cellulose to swell and activate cellulose. The ionic liquid weakens some of the hydrogen bonds between cellulose molecules by forming a competitive interaction with the hydroxyl groups of cellulose, causing the fiber to swell and increasing the accessibility of the reaction, thereby shortening the reaction time.
[0011] (2) This invention does not have any particular restrictions on the source of cellulose, whether it is commonly used microcrystalline cellulose or untreated poplar wood flour. Cellulose nanocrystals can be obtained in a short time. This is because ionic liquids not only treat the hydrogen bonds between cellulose molecules, but also degrade similar hemicellulose. Furthermore, the anions and cations of the ionic liquids interact with lignin, which can degrade some of the lignin. This makes it possible to utilize all components of biomass raw materials. Cellulose nanocrystals can be obtained from wood flour in a few hours without any pretreatment.
[0012] (3) The ionic liquids used in this invention can be reused. After simple separation treatment, they can be reused five times to prepare cellulose nanocrystals with uniform size.
[0013] (4) The present invention has mild reaction conditions, simple steps, short time required and wide source of raw materials for the preparation of cellulose nanocrystals. It can be applied to various cellulose raw materials that exist in the prior art, including the most commonly used pulp, highly crystalline microcrystalline cellulose, and even untreated wood flour. Attached Figure Description
[0014] Figure 1 Transmission microscope image of the cellulose nanocrystals prepared in Example 1;
[0015] Figure 2The images show the morphological characteristics of the cellulose nanocrystals prepared in Examples 1-3. a is an atomic force microscope image, b is the length distribution of the cellulose nanocrystals, and c is the width distribution of the cellulose nanocrystals.
[0016] Figure 3 The chemical characterization diagrams of the cellulose nanocrystals prepared in Examples 1-3 are shown below: a is the Fourier transform infrared spectrum, b is the solid-state nuclear magnetic resonance spectrum, and c is the X-ray diffraction spectrum.
[0017] Figure 4 XPS characterization images of microcrystalline cellulose and cellulose nanocrystals prepared in Example 1, where a is microcrystalline cellulose and b and c are cellulose nanocrystals prepared in Example 1.
[0018] Figure 5 Optical rotation images of microcrystalline cellulose and the cellulose nanocrystal dispersion prepared in Example 1 under a cross polarizer;
[0019] Figure 6 The images show the morphology and crystallinity of the cellulose nanocrystals prepared in the scaled-up experiment of Example 8. a is a photograph of the reaction in a 10L reactor, b is a photograph of the sample prepared in a 10L reactor, c is the XRD pattern of the samples prepared in Example 1 (H7Cl3) and Example 8 (S-H7Cl3), and d is a transmission electron microscope image of the cellulose nanocrystals prepared in the scaled-up experiment of Example 8.
[0020] Figure 7 This is a characterization diagram of the crystallinity of cellulose nanocrystals prepared using recycled experimental solvent in Example 1;
[0021] Figure 8 The growth curve of Escherichia coli was obtained from the small molecule sugar extracted from the recovered liquid in step two of Example 1. 1 is a blank aqueous solution, 2 is the small molecule sugar extracted from the recovered liquid, and 3 is a standard glucose solution.
[0022] Figure 9 Transmission microscope image of cellulose nanocrystals prepared in Example 4;
[0023] Figure 10 Transmission microscope image of cellulose nanocrystals prepared in Example 5;
[0024] Figure 11 The solid-state NMR spectrum of cellulose nanocrystals prepared in Example 6;
[0025] Figure 12 The chemical characterization diagrams for the cellulose nanocrystals prepared in Example 6 are shown below. a represents poplar wood powder, and b and c represent the cellulose nanocrystals prepared in Example 6.
[0026] Figure 13The images show the morphological characteristics of the cellulose nanocrystals prepared in Example 7. a is a transmission electron microscope image, b is a length distribution image, c is a width distribution image, and d is an XRD pattern.
[0027] Figure 14 Photograph of the cellulose nanocrystals prepared in Example 1;
[0028] Figure 15 This is a photograph of the cellulose nanocrystals prepared in Example 6. Detailed Implementation
[0029] Specific Implementation Method 1: This implementation method is a rapid and green preparation method for cellulose nanocrystals based on a mixed ionic liquid system, which is carried out according to the following steps:
[0030] 1. A dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose and an acidic ionic liquid that catalyzes the breaking of glycosidic bonds are heated and mixed evenly to obtain a mixed ionic liquid. The lignocellulose raw material is added to the mixed ionic liquid to react and obtain a reaction system. The antisolvent is added to the reaction system to terminate the reaction and obtain a diluted reaction system.
[0031] Second, the diluted reaction system is allowed to stand, then centrifuged multiple times, and finally the solid product is added to a solvent for mechanical treatment, thus completing the rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system.
[0032] The lignocellulose raw materials described in this embodiment encompass any natural biomass, industrial semi-finished products, or synthetically derived substances rich in cellulose components. This includes, but is not limited to, the following group: woody biomass (such as logs, branches, or processing residues of coniferous and broadleaf trees), herbaceous and agricultural waste (such as various straws, bagasse, bamboo, and reeds), bast and specialty plant fibers (such as cotton, cotton linters, and various hemp fibers), industrial pulp and recycled resources (such as sulfate pulp, dissolving pulp, microcrystalline cellulose, and waste paper pulp), and one or more of non-plant-derived cellulose (such as bacterial cellulose, sea squirts, or algal cellulose). Furthermore, the lignocellulose raw materials may be produced without any chemical delignification or dehemicellulose pretreatment.
[0033] In this embodiment, after the recovered liquid is filtered and distilled or electrodialysis to remove impurities and moisture, the resulting mixed ionic liquid can be directly returned for recycling in the preparation of the next batch of cellulose nanocrystals.
[0034] This embodiment uses a mixed ionic liquid system as the reaction medium. This system exhibits excellent solubility selectivity and catalytic activity. Utilizing the synergistic effect of the mixed ionic liquid reaction system, the swelling of cellulose and the hydrolysis of its amorphous regions are simultaneously achieved. No cumbersome physical or chemical pretreatment of the raw materials is required; it can be directly applied to all components of biomass raw materials (such as poplar wood powder, corn stalk powder, etc.). Compared with traditional methods, it has the following significant advantages:
[0035] 1. Highly efficient and convenient process: The reaction time is greatly shortened. MCC can complete the conversion from raw materials to nanocrystals in 15 minutes, and the separation of all components of biomass raw materials such as poplar powder can be completed in as little as 1 hour.
[0036] 2. Green and environmentally friendly with low cost: The mixed ionic liquids and related reagents in the reaction system can be efficiently recovered and reused, which significantly reduces production costs and environmental impact.
[0037] 3. Wide applicability of raw materials: It breaks through the dependence of traditional methods on high-purity raw materials and realizes the direct high-value utilization of agricultural and forestry waste.
[0038] The beneficial effects of this embodiment are:
[0039] (1) In this embodiment, a dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose is used to swell and activate cellulose. The ionic liquid weakens some of the hydrogen bonds between cellulose molecules by forming a competitive interaction with the hydroxyl groups of cellulose, causing the fiber to swell and increasing the accessibility of the reaction, thereby shortening the reaction time.
[0040] (2) This embodiment does not have any particular restrictions on the source of cellulose, whether it is commonly used microcrystalline cellulose or untreated poplar wood flour. Cellulose nanocrystals can be obtained in a short time because ionic liquids not only treat the hydrogen bonds between cellulose molecules, but also degrade similar hemicellulose. Furthermore, the anions and cations of the ionic liquids interact with lignin, which can degrade some of the lignin. This makes it possible to utilize all components of biomass raw materials, and cellulose nanocrystals can be obtained from wood flour in a few hours without any pretreatment.
[0041] (3) The ionic liquids used in this embodiment can be reused. After simple separation treatment, they can still be used five times to prepare cellulose nanocrystals with uniform size.
[0042] (4) The reaction conditions for preparing cellulose nanocrystals in this embodiment are mild, the steps are simple, the required time is short, and the raw material sources are wide. It can be applied to various cellulose raw materials that exist in the existing technology, including the most commonly used pulp, highly crystalline microcrystalline cellulose, and even untreated wood flour.
[0043] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: In step one, at a temperature of 60℃~140℃, a dissolving / swelling ionic liquid that disrupts cellulose hydrogen bonds and an acidic ionic liquid that catalyzes glycosidic bond breaking are heated and mixed evenly to obtain a mixed ionic liquid. At a temperature of 100℃~140℃, the lignocellulose raw material is added to the mixed ionic liquid and reacted for 10 min~4 h to obtain a reaction system. An antisolvent is added to the reaction system to terminate the reaction, resulting in a diluted reaction system. Everything else is the same as in Specific Implementation Method One.
[0044] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in the following ways: the mass ratio of the dissolving / swelling ionic liquid that breaks cellulose hydrogen bonds to the acidic ionic liquid that catalyzes glycosidic bond breaking in step one is 10:(1~100); the mass ratio of the lignocellulose raw material to the mixed ionic liquid in step one is 1:(5~200); the mass ratio of the reaction system to the antisolvent in step one is 1:(3~10); and the particle size of the lignocellulose raw material in step one is 20 mesh to 600 mesh. Everything else is the same as in Specific Implementation Method One or Two.
[0045] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose in step one is one or a combination of several of imidazole halosalts, imidazole carboxylates, and choline ionic liquids; the acidic ionic liquid that catalyzes the breaking of glycosidic bonds in step one is one or a combination of several of Brønsted acidic ionic liquids, Lewis acidic ionic liquids, and proton-type ionic liquids. Everything else is the same as in Specific Implementation Methods One to Three.
[0046] Specific Embodiment Five: This embodiment differs from Specific Embodiments One to Four in that: the imidazole halosalt is one or a combination of two of 1-butyl-3-methylimidazolium chloride and 1-allyl-3-methylimidazolium chloride; the imidazole carboxylate is one or a combination of two of 1-ethyl-3-methylimidazolium acetate and 1-butyl-3-methylimidazolium acetate; and the choline ionic liquid is one or a combination of two of choline lysine salt and choline acetate. Everything else is the same as in Specific Embodiments One to Four.
[0047] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the Brønsted acidic ionic liquid is a sulfonic acid or carboxyl-functionalized imidazole ionic liquid; the sulfonic acid or carboxyl-functionalized imidazole ionic liquid is one or a combination of several of 1-butylsulfonic-3-methylimidazolium hydrogen sulfate, 1-butyl-3-methylimidazolium hydrogen sulfate, and 1-carboxymethyl-3-methylimidazolium hydrogen sulfate; the Lewis acidic ionic liquid is a complex system of metal halide and ionic liquid, the metal halide being FeCl3, ZnCl2, or AlCl3; the proton-type ionic liquid is one or a combination of several of 1-methylimidazolium hydrogen sulfate and 1-methylimidazolium chloride. Everything else is the same as in Specific Implementation Methods One to Five.
[0048] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the lignocellulosic raw material mentioned in step one is a biomass raw material or a cellulose raw material. Everything else is the same as in Specific Implementation Methods One to Six.
[0049] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that: the biomass raw material is one or a combination of several of the following: wood flour, crop straw, bamboo flour, cotton linters, and bagasse; the cellulose raw material is one or a combination of several of the following: plant fiber, pulp fiber, microcrystalline cellulose, and α-cellulose. Everything else is the same as in Specific Implementation Methods One to Seven.
[0050] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the antisolvent mentioned in step one is one or a combination of several of water, ethanol, acetone, and acetonitrile. Everything else is the same as in Specific Implementation Methods One to Eight.
[0051] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that: the centrifugal separation in step two is specifically carried out at a centrifuge speed of 6000 rpm to 11000 rpm for 5 min to 15 min, and the centrifugation is repeated 2 to 8 times to obtain a solid product and a recovered liquid; the mechanical treatment in step two is one or a combination of ultrasonic dispersion, high-pressure homogenization, ball milling, and high-speed shearing. Everything else is the same as in Specific Implementation Methods One to Nine.
[0052] The beneficial effects of the present invention are verified using the following embodiments:
[0053] Example 1:
[0054] A rapid and green method for preparing cellulose nanocrystals based on a mixed ionic liquid system is described, comprising the following steps:
[0055] 1. Under the condition of 120℃, 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) and 1-butyl-3-methylimidazolium hydrogen sulfate ([BMIM]HSO4) were heated and mixed evenly to obtain a mixed ionic liquid (10g). Under the condition of 120℃, microcrystalline cellulose was added to the mixed ionic liquid and reacted for 15min to obtain a reaction system. Deionized water was added to the reaction system to terminate the reaction and obtain a diluted reaction system.
[0056] The mass ratio of 1-butyl-3-methylimidazolium hydrogen sulfate to 1-butyl-3-methylimidazolium chloride is 7:3; the mass ratio of microcrystalline cellulose to mixed ionic liquid is 1:20; the mass ratio of the reaction system to deionized water is 1:3; and the particle size of the microcrystalline cellulose is 25 micrometers to 65 micrometers.
[0057] 2. Allow the diluted reaction system to stand, then centrifuge at 10,000 rpm for 5 minutes. Repeat the centrifugation process 4 times to obtain the solid product and the recovered liquid. Add the solid product to water and sonicate for 5 minutes at a power of 300W to obtain a cellulose nanocrystal suspension.
[0058] The concentration of the cellulose nanocrystal suspension is 0.5 wt.%.
[0059] The cellulose nanocrystals (named H7Cl3) in the cellulose nanocrystal suspension described in Example 1 have an average length of 105.7 nm, an average diameter of 6.8 nm, and are of type I crystal structure with a crystallinity of 85.2%. The yield of cellulose nanocrystals is 54%.
[0060] Example 2: This example differs from Example 1 in that the mass ratio of 1-butyl-3-methylimidazolium hydrogen sulfate to 1-butyl-3-methylimidazolium chloride in step one is 5:5. Everything else is the same as in Example 1.
[0061] The cellulose nanocrystals (named H5Cl5) in the cellulose nanocrystal suspension described in Example 2 have an average length of 145.3 nm, an average diameter of 8.4 nm, and are of type I crystal structure with a crystallinity of 74.5%. The yield of cellulose nanocrystals is 52%.
[0062] Example 3: This example differs from Example 1 in that the mass ratio of 1-butyl-3-methylimidazolium hydrogen sulfate to 1-butyl-3-methylimidazolium chloride in step one is 3:7. Everything else is the same as in Example 1.
[0063] The cellulose nanocrystals (named H3Cl7) in the cellulose nanocrystal suspension described in Example 3 have an average length of 205.1 nm, an average diameter of 9.3 nm, and are of type I crystal structure with a crystallinity of 71.6%. The yield of cellulose nanocrystals is 47%.
[0064] Example 4:
[0065] A rapid and green method for preparing cellulose nanocrystals based on a mixed ionic liquid system is described, comprising the following steps:
[0066] 1. Under the condition of 140℃, 1-butyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium hydrogen sulfate were heated and mixed evenly to obtain a mixed ionic liquid. Under the condition of 140℃, corn straw powder was added to the mixed ionic liquid and reacted for 1 hour to obtain a reaction system. Deionized water was added to the reaction system to terminate the reaction and obtain a diluted reaction system.
[0067] The mass ratio of 1-butyl-3-methylimidazolium hydrogen sulfate to 1-butyl-3-methylimidazolium chloride is 7:3; the mass ratio of corn stalk powder to mixed ionic liquid is 1:100; the mass ratio of reaction system to deionized water is 1:5; and the particle size of corn stalk powder is 100 mesh to 200 mesh.
[0068] 2. Allow the diluted reaction system to stand, then centrifuge at 10,000 rpm for 5 minutes. Repeat the centrifugation process 5 times to obtain the solid product and the recovered liquid. Add the solid product to water and sonicate for 10 minutes at a power of 300W to obtain a cellulose nanocrystal suspension.
[0069] The concentration of the cellulose nanocrystal suspension is 0.5 wt.%.
[0070] The cellulose nanocrystal suspension described in Example 4 has an average length of 148 nm, an average diameter of 5 nm, and the cellulose nanocrystals have a type I crystal structure with a crystallinity of 61% and a yield of 15%.
[0071] Example 5: This example differs from Example 4 in that the corn stalk powder is replaced with bamboo powder in step one. Everything else is the same as in Example 4.
[0072] In Example 5, the cellulose nanocrystal suspension contained cellulose nanocrystals with an average length of 150 nm, an average diameter of 5 nm, a type I crystal structure, a crystallinity of 66%, and a yield of 17%.
[0073] Example 6: This example differs from Example 4 in that the corn stalk powder in step one is replaced with poplar powder. Everything else is the same as in Example 4.
[0074] The cellulose nanocrystal suspension described in Example 6 has an average length of 137 nm, an average diameter of 5 nm, and the cellulose nanocrystals have a type I crystal structure with a crystallinity of 75% and a yield of 19%.
[0075] Example 7: This example differs from Example 6 in that the mass ratio of poplar wood powder to the mixed ionic liquid in step one is 1:20; and in step one, the poplar wood powder is added to the mixed ionic liquid and reacted for 4 hours at a temperature of 140°C. Everything else is the same as in Example 6.
[0076] The cellulose nanocrystals (LCNCs) in the cellulose nanocrystal suspension described in Example 7 have an average length of 199 nm, an average diameter of 8 nm, and are of type I crystal structure with a crystallinity of 73.4%. The yield of cellulose nanocrystals is 27%.
[0077] Example 8 is a scaled-up experiment of Example 1. The difference between this example and Example 1 is that the mass of the mixed ionic liquid in step one is 4 kg. Everything else is the same as in Example 1.
[0078] Figure 1 Transmission electron microscopy (TEM) images show the cellulose nanocrystals prepared in Example 1. TEM reveals that the cellulose nanocrystals prepared in Example 1 exhibit a typical needle-like structure, with the fiber morphology resembling rod-shaped crystals. Notably, approximately 70% of the cellulose nanocrystals in H7Cl3 have a length of 70 nm to 120 nm, indicating that the synergistic effect between [BMIM]HSO4 and [BMIM]Cl enhances the accessibility of the cellulose structure and promotes efficient formation of cellulose nanocrystals.
[0079] Figure 2 The images show the morphological characteristics of the cellulose nanocrystals prepared in Examples 1-3. a) is an atomic force microscopy (AFM) image, b) shows the length distribution of the cellulose nanocrystals, and c) shows the width distribution of the cellulose nanocrystals. AFM analysis confirmed the formation of cellulose nanocrystals with a characteristic needle-like morphology. With increasing [BMIM]HSO4 content, the length of the cellulose nanocrystals significantly decreased from 205.1 ± 30.6 nm to 105.7 ± 29.5 nm, while the diameter also decreased from 9.3 ± 2.9 nm to 6.8 ± 2.2 nm. Furthermore, the higher the [BMIM]HSO4 content, the narrower the particle size distribution.
[0080] Figure 3The images show the chemical characterization of the cellulose nanocrystals prepared in Examples 1-3: a) Fourier transform infrared spectrum, b) solid-state nuclear magnetic resonance spectrum, and c) X-ray diffraction spectrum. The FTIR spectra of cellulose nanocrystals and microcrystalline cellulose (MCC) show similar characteristic peaks, indicating that the cellulose backbone has not undergone significant changes. 13 In the C10 NMR spectrum, the signals after treatment (C4′ at 83.7 ppm and C6′ at 62.1 ppm) were weakened, while the signals corresponding to the more ordered cellulose domains (C4′ at 88.5 ppm and C6′ at 64.9 ppm) remained relatively unchanged. Correspondingly, XRD analysis showed that the apparent crystallinity index (CrI) of H7Cl3 reached a maximum of 85.2%. To further evaluate the changes in cellulose crystalline domains, the crystal width (L) was calculated from the (200) diffraction peak according to the Scherrer equation. 200 The calculated (L) 200 The value decreased slightly from about 5.0 nm in MCC to 4.3 nm to 4.8 nm in the treated cellulose nanocrystal samples, with 4.5 nm in Example 1, 4.3 nm in Example 2, and 4.8 nm in Example 3, indicating that the crystal domains were largely preserved during solvent treatment.
[0081] Figure 4 XPS characterization images of microcrystalline cellulose and cellulose nanocrystals prepared in Example 1 are shown. a) represents microcrystalline cellulose, and b and c) represent cellulose nanocrystals prepared in Example 1. X-ray photoelectron spectroscopy (XPS) spectra show that C and O are the main components, and the oxygen-to-carbon ratio increased from 61.6% to 67.7% after solvent treatment. The C peak at 284.8 eV was weakened, while the CO characteristic peak at 286.4 eV was enhanced, indicating that more hydroxyl groups were exposed after the reaction. Compared with MCC, H7Cl3 showed an additional S 2p signal in the XPS scan, indicating that partial sulfate hemiester functionalization occurred on the accessible hydroxyl groups of H7Cl3.
[0082] Figure 5 Optical rotation images of microcrystalline cellulose and the cellulose nanocrystal dispersion prepared in Example 1 under a cross polarizer; elemental analysis of the products of Examples 1-3 was performed, and it was found that with the increase of the proportion of [BMIM]HSO4, the S content in the sample increased, and the corresponding zeta potential also increased, proving that some sulfate half ester was introduced into the product to increase its stability and surface electronegativity. As shown in Table 1, the zeta potential increased to -21.5 mV.
[0083] Table 1
[0084]
[0085] Figure 6The images show the morphology and crystallinity characterization of the cellulose nanocrystals prepared in the scaled-up experiment of Example 8. a) is a photograph of the reaction in a 10L reactor; b) is a photograph of the sample prepared in a 10L reactor; c) are the XRD patterns of the samples prepared in Example 1 (H7Cl3) and Example 8 (S-H7Cl3); and d) is a transmission electron microscope image of the cellulose nanocrystals prepared in the scaled-up experiment of Example 8. The crystallinity of the cellulose nanocrystals in the scaled-up experiment was 84.5%. The nanocrystals exhibited a width distribution of 3nm~7nm and a length of 100nm~200nm, with a typical rod-like structure, indicating that the prepared cellulose nanocrystals had the same superior performance as those in Example 1. Therefore, this method has good process operability, and the experimental results show that the morphology and crystallinity of the samples produced on a large scale are basically consistent, demonstrating the stability and superiority of this method in industrial production.
[0086] The solvent used in Example 1 can be recycled. After the reaction in Step 2, the product and solvent are separated by centrifugation. The resulting recovered solution is filtered for impurities using a 0.22-micron microporous membrane and then treated by electrodialysis (referencing patent CN110527751A). The specific conditions are as follows: 0.25 L of unused [BMIM]HSO4 and [BMIM]Cl (mass ratio 7:3) mixed solution (15 g / L) is circulated in the concentration chamber; 1.0 L of solution (15 g / L) prepared using the recovered solution after removing water in Step 2 of Example 1 is circulated in the desalination chamber; and unused [BMIM]HSO4 and [BMIM]Cl (mass ratio 7:3) (20 g / L) are circulated in the electrode chamber. A constant voltage of 7 V is applied until the conductivity of the diluted solution drops to 100 μS / cm. -1 Alternatively, once the current reaches a steady state, the power is cut off. After removing moisture through vacuum distillation, the recycled experimental solvent is obtained in the concentration chamber and recycled according to the method in Example 1. The desalination chamber contains the recovered small-molecule sugar solution, which can be used after rotary evaporation concentration.
[0087] Figure 7 The image shows the crystallinity characterization of cellulose nanocrystals prepared using recycled experimental solvent in Example 1. The solvent used in Example 1 can be recycled and reused. After five cycles, there was no significant difference in crystallinity, indicating that it has the characteristic of being reusable, which can reduce production costs and alleviate the burden of wastewater treatment.
[0088] Figure 8The growth curve of *E. coli* was obtained from the small molecule sugar extracted from the recovered liquid in step two of Example 1. 1 is a blank aqueous solution, 2 is the small molecule sugar extracted from the recovered liquid, and 3 is a standard glucose solution. Simultaneously, electrodialysis was used to recover the degraded small molecule sugars from the solvent. After rotary evaporation, a sugar solution concentrated to 4 g / L was prepared. The growth curve of *E. coli* was tested in a 96-well plate. *E. coli* showed high activity in the recovered sugar solution, indicating its fermentation potential.
[0089] Figure 9 The image shows a transmission electron microscope (TEM) image of the cellulose nanocrystals prepared in Example 4. TEM reveals that the cellulose nanocrystals prepared in Example 4 have a typical needle-like structure, with a diameter between 3 nm and 10 nm and a length between 100 nm and 200 nm, consistent with the typical morphology of lignocellulose nanocrystals. The TEM image also shows some lignin particles, indicating the successful preparation of lignin-containing cellulose nanocrystals.
[0090] Figure 10 The image shows a transmission electron microscope (TEM) image of the cellulose nanocrystals prepared in Example 5. TEM reveals that the cellulose nanocrystals prepared in Example 5 have a typical needle-like structure, with a diameter between 3 nm and 10 nm and a length of approximately 150 nm, consistent with the typical morphology of lignocellulose nanocrystals. The TEM image also shows some lignin particles, indicating the successful preparation of lignin-containing cellulose nanocrystals.
[0091] Figure 11 The solid-state NMR spectrum of the cellulose nanocrystals prepared in Example 6 is shown. The solid-state NMR spectrum is compared with that of lignin-containing cellulose nanocrystals prepared from natural biomass and poplar wood. The peak positions corresponding to the disordered region in the cellulose structure are reduced, and the peaks of the benzene ring and its aromatic side chains of lignin are also significantly reduced, indicating that some of these components are removed during the solvent treatment.
[0092] Figure 12 The chemical characterization diagrams for the cellulose nanocrystals prepared in Example 6 are shown, with a representing poplar wood powder and b and c representing the cellulose nanocrystals prepared in Example 6. XPS analysis showed that, compared to poplar, the CC / CH signal in the C 1s spectrum of LCNCs was weakened, while the CO peak was enhanced. Overall, these complementary characterization results indicate that hemicellulose and lignin were partially removed, while cellulose was exposed. Furthermore, the S 2p spectrum of LCNCs showed a signal corresponding to the sulfate hemiester group, confirming that partial sulfation occurred during the treatment process.
[0093] Figure 13The images show the morphological characterization of the cellulose nanocrystals prepared in Example 7: a) transmission electron microscopy, b) length distribution, c) width distribution, and d) XRD pattern. Transmission electron microscopy (TEM) shows that the cellulose nanocrystals prepared in Example 7 have a typical needle-like structure with a diameter of approximately 7 nm and a length of approximately 200 nm, consistent with the typical morphology of lignocellulose nanocrystals. Furthermore, compared to the original natural biomass, its crystallinity increased from 57.1% to 73.4%, indicating that a large number of disordered regions have been removed, demonstrating the superior performance of this solvent in separating lignocellulosic components.
[0094] Figure 14 Photograph of the cellulose nanocrystals prepared in Example 1; Figure 15 The image shows a photograph of the cellulose nanocrystals prepared in Example 6. As can be seen from the figure, the method of the example has industrial stability and process advantages. The prepared sample has good stability, high crystallinity, and can be mass-produced.
Claims
1. A rapid and green method for preparing cellulose nanocrystals based on a mixed ionic liquid system, characterized in that... It is done in the following steps:
1. A dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose and an acidic ionic liquid that catalyzes the breaking of glycosidic bonds are heated and mixed evenly to obtain a mixed ionic liquid. The lignocellulose raw material is added to the mixed ionic liquid to react and obtain a reaction system. The antisolvent is added to the reaction system to terminate the reaction and obtain a diluted reaction system. Second, the diluted reaction system is allowed to stand, then centrifuged multiple times, and finally the solid product is added to a solvent for mechanical treatment, thus completing the rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system.
2. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... In step one, at a temperature of 60℃~140℃, a dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose and an acidic ionic liquid that catalyzes the breaking of glycosidic bonds are heated and mixed evenly to obtain a mixed ionic liquid. At a temperature of 100℃~140℃, the lignocellulose raw material is added to the mixed ionic liquid and reacted for 10 min~4 h to obtain a reaction system. The antisolvent is added to the reaction system to terminate the reaction and obtain a diluted reaction system.
3. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... The mass ratio of the dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose to the acidic ionic liquid that catalyzes the breaking of glycosidic bonds in step one is 10:(1~100); the mass ratio of the lignocellulose raw material to the mixed ionic liquid in step one is 1:(5~200); the mass ratio of the reaction system to the antisolvent in step one is 1:(3~10); and the particle size of the lignocellulose raw material in step one is 20 mesh to 600 mesh.
4. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... The dissolving / swelling ionic liquid that breaks the hydrogen bonds of cellulose mentioned in step one is one or a combination of several of the following: imidazole halide salts, imidazole carboxylates, and choline ionic liquids; the acidic ionic liquid that catalyzes the breaking of glycosidic bonds mentioned in step one is one or a combination of several of the following: Brønsted acidic ionic liquids, Lewis acidic ionic liquids, and proton-type ionic liquids.
5. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 4, characterized in that... The imidazole halosalt is one or a combination of 1-butyl-3-methylimidazolium chloride and 1-allyl-3-methylimidazolium chloride; the imidazole carboxylate is one or a combination of 1-ethyl-3-methylimidazolium acetate and 1-butyl-3-methylimidazolium acetate; the choline ionic liquid is one or a combination of choline lysine salt and choline acetate.
6. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 4, characterized in that... The Brønsted acidic ionic liquid is a sulfonic acid or carboxyl-functionalized imidazole ionic liquid; the sulfonic acid or carboxyl-functionalized imidazole ionic liquid is one or a combination of several of 1-butylsulfonic-3-methylimidazolium hydrogen sulfate, 1-butyl-3-methylimidazolium hydrogen sulfate, and 1-carboxymethyl-3-methylimidazolium hydrogen sulfate; the Lewis acidic ionic liquid is a complex system of metal halide and ionic liquid, the metal halide being FeCl3, ZnCl2, or AlCl3; the proton-type ionic liquid is one or a combination of several of 1-methylimidazolium hydrogen sulfate and 1-methylimidazolium chloride.
7. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... The lignocellulose raw material mentioned in step one is a biomass raw material or a cellulose raw material.
8. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 7, characterized in that... The biomass raw material is one or a combination of several of the following: wood flour, crop straw, bamboo flour, cotton linters, and bagasse; the cellulose raw material is one or a combination of several of the following: plant fiber, pulp fiber, microcrystalline cellulose, and α-cellulose.
9. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... The antisolvent mentioned in step one is one or a combination of several of water, ethanol, acetone and acetonitrile.
10. The rapid and green preparation method of cellulose nanocrystals based on a mixed ionic liquid system according to claim 1, characterized in that... The centrifugation separation described in step two is specifically carried out at a centrifuge speed of 6000 rpm to 11000 rpm for 5 min to 15 min, and the centrifugation separation is repeated 2 to 8 times to obtain solid products and recovery liquid; the mechanical treatment in step two is one or a combination of ultrasonic dispersion, high pressure homogenization, ball milling and high-speed shearing.
Citation Information
Patent Citations
Method for removing small-molecule sugar in ionic liquid system
CN110527751A
